Parametric modelling of architectural surfaces - Pitts, G.; Datta, Sambit (National Yunlin University of Science and Technology, 2009)
Parametric modelling is gaining in popularity as both a fabrication and design tool, but its application in the architectural design industry has not been widely explored. Parametric modelling has the ability to generate complex forms with intuitively reactive components, allowing designers to express and fabricate structures previously too laborious and geometrically complex to realise. This allows designers to address a project at both the macro and micro levels of resolution in the governing control surface and the individual repetitive component. This two level modelling control, of component and overall surface, can allow designers to explore new types of form generation subject to parametric constraints. Shading screens have been selected as the focus for this paper and are used as a medium to explore form generation within a given set of functional parameters. Screens can have many applications in a building but for the purpose of the following case studies, lighting quality and passive sun control are the main functional requirement. A set of screen components have been designed within certain shading parameters to create a generic component that can automatically adapt to any given climatic conditions. These will then be applied to surfaces of varying degrees of geometric complexity to be analysed in their ability to correctly tessellate and create a unified screening array true to the lighting requirements placed on the generic component.